Pengaruh Social Media Marketing, Event Marketing Terhadap Keputusan Pembelian Dengan Customer Engagement - M. Ikhwan Syarif; Suhairi; Siti Aisyah (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2025)
This study aims to analyze the influence of social media marketing and event marketing on purchasing decisions, with customer engagement as an intervening variable in the Mobile Legends game in Medan City. The population in this study includes all Mobile Legends players in Medan City. The sampling technique was carried out using a non-probability sampling method with a purposive sampling approach. The number of samples used was 150 respondents, which was determined using the Cochran formula. The data analysis technique used was SEM-PLS using SmartPLS software. The results of the study showed that SMM had a significant influence on KP and CE, EM had a significant influence on KP and CE. While CE did not have a significant effect on KP. SMM also had no significant effect on KP through CE, as well as EM which had no significant effect on KP through CE.